2014
DOI: 10.3892/etm.2014.1895
|View full text |Cite
|
Sign up to set email alerts
|

Ulcerative colitis combined with acute interstitial lung disease and airway disease: A case report and literature review

Abstract: The aim of this study was to investigate the clinical features of ulcerative colitis (UC) combined with acute interstitial lung disease (ILD). One case with acute UC combined with ILD and airway disease was reported, and the pathological diagnosis of previous cases of UC combined with ILD was retrospectively analyzed according to the corresponding literature. The present case concerned a male patient with UC who presented with dry cough and progressive dyspnea. The chest computed tomography (CT) images showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…BOOP can be caused by inhalation or medication injuries and has an acute or subacute onset with fever, cough, dyspnea, and pleuritic chest pain. 21 The treatment of patients with IBD can cause lung complications. The use of azathioprine (AZA) and 6-mercaptopurine (6-MP) may cause interstitial pneumonia, BOOP, chronic fibrosis/pneumonitis, and pulmonary edema.…”
Section: Pulmonary Manifestationsmentioning
confidence: 99%
“…BOOP can be caused by inhalation or medication injuries and has an acute or subacute onset with fever, cough, dyspnea, and pleuritic chest pain. 21 The treatment of patients with IBD can cause lung complications. The use of azathioprine (AZA) and 6-mercaptopurine (6-MP) may cause interstitial pneumonia, BOOP, chronic fibrosis/pneumonitis, and pulmonary edema.…”
Section: Pulmonary Manifestationsmentioning
confidence: 99%
“…Ulcerative colitis (UC) predominantly impacts the joints, skin, liver, and eyes in addition to its intestinal signs [2]. Despite the rarity of UC associated to pulmonary diseases in clinical settings, it is crucial to identify pulmonary problems as soon as possible in order to reduce patient mortality [3]. As shown in (Table 1), the range of lung involvement in IBDs ranges from asymptomatic abnormal involvement to interstitial lung disease (ILD) [4].…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have demonstrated that BMSCs are able to grow and participate in the development of lung tissue. The administration of BMSCs has been shown to ameliorate fibrotic injuries, suggesting the possibility that stem cell-based therapies may be developed as an effective intervention against pulmonary fibrosis (15)(16)(17)(18). BMSCs exist in numerous types of human tissue, possess multidirectional differentiation potential and may be obtained from a variety of tissues.…”
mentioning
confidence: 99%